2016
DOI: 10.5114/wo.2016.60071
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-emptive analgesia on the level of postoperative pain in women undergoing surgery for breast neoplasm

Abstract: Aim of the studyDynamic development of research on pain has resulted in the formulation of the concept of pre-emptive analgesia, which involves administration of analgesics before the first pain-producing stimulus appears. It is meant to prevent increased sensitivity to pain in the postoperative period. The aim of this study was to assess the possibilities of modifying the intensity of postoperative pain evaluated with the visual analogue scale (VAS) in patients after surgical treatment for breast neoplasm off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…T he idea of preemptive analgesia was first proposed by Woolf in Harvard Medical School 8 , with the purpose to block the pain sensation center before harmful stimulation occurs, to inhibit the center sensitization and to raise the threshold of pain sensation. Recently, there have been many studies published on the preoperative use of local anesthesia agents, including opiates and NSAIDS [9][10][11][12] , but the value of preemptive analgesia is still controversial [13][14][15] . It has been proved that synthesis of COX-2 increases after inflammatory stimulation, and increases the production of prostaglandins, which induces inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
“…T he idea of preemptive analgesia was first proposed by Woolf in Harvard Medical School 8 , with the purpose to block the pain sensation center before harmful stimulation occurs, to inhibit the center sensitization and to raise the threshold of pain sensation. Recently, there have been many studies published on the preoperative use of local anesthesia agents, including opiates and NSAIDS [9][10][11][12] , but the value of preemptive analgesia is still controversial [13][14][15] . It has been proved that synthesis of COX-2 increases after inflammatory stimulation, and increases the production of prostaglandins, which induces inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
“…Data was collected at 6, 12, 18, and 24 hours post-operatively. The authors found that patients had significantly less pain post-operatively when they received preemptive pain medication (in this case, tramadol or ketoprofen) than those patients who did not receive any medication, thus highlighting the effectiveness of preemptive pain medication on post-operative pain control (Wegorowski et al, 2016).…”
Section: Preemptive Pain Medicationmentioning
confidence: 96%
“…When pain is left untreated, hyperalgesia, alterations in pain processing and chronic pain may ultimately develop (Kelly, et al, 2001). Chronic pain may develop from acute post-operative pain in up to 50% of patients after surgeries such as amputations, breast surgery, or inguinal hernioplasty (Wegorowski, et al, 2016).…”
Section: Painmentioning
confidence: 99%
See 2 more Smart Citations